2018
DOI: 10.1039/c8ta05291c
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the efficiency of perovskite solar cells using mesoscopic zinc-doped TiO2 as the electron extraction layer through band alignment

Abstract: A meso-Zn:TiO2 electron extraction layer exhibits the optimal band alignment with CH3NH3PbI3, and the champion PCE of the PSC is 18.3%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 73 publications
1
35
0
Order By: Relevance
“…The synthesis of mesoporous zinc‐doped TiO 2 (meso‐Zn:TiO 2 ) paste was based on our previous work . Briefly, a 12.5 g of titanium isopropoxide and 5.0 mL of 2‐propanol were mixed together.…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis of mesoporous zinc‐doped TiO 2 (meso‐Zn:TiO 2 ) paste was based on our previous work . Briefly, a 12.5 g of titanium isopropoxide and 5.0 mL of 2‐propanol were mixed together.…”
Section: Methodsmentioning
confidence: 99%
“…The result showed that Ni 2+ doping could boost the conductivity of α‐Fe 2 O 3 and decrease the charge accumulation at the perovskite/ETL interface, leading to improved photovoltaic performance with negligible hysteresis. Wu et al [ 202 ] demonstrated Zn 2+ ‐doped TiO 2 NPs as a mesoscopic ETL via combining sol–gel and hydrothermal methods (Figure 11d). They found that the TiO 2 achieved more appropriate energy alignment with the perovskite photoactive layer compared with pure TiO 2 .…”
Section: Doping Of Semiconductor Oxides Etlsmentioning
confidence: 99%
“…For the TiO 2 -based EEL, it can be classified into two types, mesoporous-structured TiO 2 layer and TiO 2 compact layer (Wu et al, 2018b;Chen et al, 2019). The mesoporous-structured TiO 2 layer must be calcined at above 400 • C to remove the organic binder (e.g., ethyl cellulose) and form the porous structure (Wu et al, 2018a). However, the high-temperature calcination leads to cost increment and energy consumption, and it is not conducive to the low-temperature process.…”
Section: Low-temperature Tio 2 Electron Extraction Layermentioning
confidence: 99%
“…The p-i-n structured PSC is based on the organic solar cells having ITO/p-type material (HTL)/perovskite/n-type material (EEL)/metal electrode (Heo et al, 2015;Fan et al, 2018;Mali et al, 2018). In contrast, n-i-p structured PSC is adopted to construct DSSC with structure FTO/n-type material (EEL)/perovskite/p-type material (HTL)/metal electrode (Chan et al, 2017;Wu et al, 2018a). Many n-type materials, including TiO 2 , Al 2 O 3 , ZnO, ZrO 2 , and SnO 2 , are often used as electron extraction layer (EEL) for PSC due to the appropriate energy band alignment with perovskite absorber (Anaraki et al, 2016;Che et al, 2016;Zhang et al, 2017Zhang et al, , 2018Wu et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation